1980
DOI: 10.1139/z80-153
|View full text |Cite
|
Sign up to set email alerts
|

Serum gonadotropin levels in mature male goldfish in response to luteinizing hormone – releasing hormone (LH-RH) and des-Gly10-[D-Ala6]-LH-RH ethylamide

Abstract: Sexually mature male goldfish, acclimated to 12–14 °C, were injected intraperitoneally with luteinizing hormone – releasing hormone (LH-RH) or the superactive analogue des-Gly10-[D-Ala6]-LH-RH ethylamide (G-A-LH-RH-E). Treatments were a single injection, two injections 12 h apart, and three injections 24 h apart at dosages of 0.1, 0.5, and 1.0 μg/g body weight. Blood samples were taken at 1 or 1.5, 6, and 24 h after the last injection for measurement of serum gonadotropin (GtH) by radioimmunoassay. Serum GtH l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The analogue was effective in stimulat ing GtH release in female goldfish when administered as two intraperitoneal injections, 12 h apart, as in previous ex periments using male goldfish [25]; with this schedule the first injection is thought to potentiate the action of the second injection. DA injected intraperitoneally after the second LHRH-A injection decreased, at 2 h after DA ad ministration, the elevated serum GtH levels induced by LHRH-A.…”
Section: Discussionmentioning
confidence: 68%
“…The analogue was effective in stimulat ing GtH release in female goldfish when administered as two intraperitoneal injections, 12 h apart, as in previous ex periments using male goldfish [25]; with this schedule the first injection is thought to potentiate the action of the second injection. DA injected intraperitoneally after the second LHRH-A injection decreased, at 2 h after DA ad ministration, the elevated serum GtH levels induced by LHRH-A.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, increasing the temperature of acclimation of carp from 25-30°C increases their plasma androgen levels and the GSI (Kime and Manning 1986). Dose-dependent effects of GnRH-A on plasma gonadotropin or sex steroids were not observed in goldfish (Lam et al 1976;Peter 1980) and in coho salmon (Van Der Kraak et al 1983. In male flounder, an examination of 3 different doses of GnRH-A ranging from 2-200 g/kg produced remarkably similar T and 11 -KT steroid profiles with no evidence of GnRH-A dose-response effects.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be due to the larger doses of LHRHa (20 pg per g body weight) employed in the current study compared to that used in mammals ( <4 pg per g body weight). However, the longterm GtH response may be inherent in fish as it has been shown that injection of low doses of LHRH and LHRHa produce a long-term GtH response in goldfish (Peter, 1980) and coho salmon (Van Der Kraak et al, 1983).…”
Section: Discussionmentioning
confidence: 99%